Points of Interest Density Based Zooming Interface for Map Exploration on Smart Glass - Kim, Doyeon; Seo, Daeil; Yoo, Byounghyun; Ko, Heedong (HUMAN INTERFACE AND THE MANAGEMENT OF INFORMATION: INFORMATION, KNOWLEDGE AND INTERACTION DESIGN, HCI INTERNATIONAL 2017, PT I, 2017)
Smart glass devices have become popular in our daily lives, and many people have applied its advantages to their application fields. In particular, smart glass has the advantage of receiving desired information by maintaining their context of the real world without dispersing their attention. Smart glass is also widely used to obtain information about points of interest with map interfaces. However, smart glass has an insufficient user interface with which to interact with its map applications via the smart glass. This problem restricts the map's ability to provide specific functions and makes users feel constrained compared to handheld devices. In this paper, we focus on a map exploration method for smart glass to solve the limitations of map interaction via the smart glass. We propose an interaction design with zooming interface based on region's point of interest density. This approach is intended for a region search without any other interaction tools. Users search and browse their regions of interest with the smart glass by using the proposed method.